Clinical Trial Research on Mongolian Medical Warm Acupuncture in Treating Insomnia. (5th December 2016) - Bo, Agula; Si, Lengge; Wang, Yuehong; Xiu, Lan; Wu, Rihan; Li, Yutang; Mu, Rigenjiya; Ga, Latai; Miao, Mei; Shuang, Fu; Wu, Yunhua; Jin, Qiu; et al.
Abstract : Objective. Insomnia is one of the most common sleep disorders. Hypnotics have poor long-term efficacy. Mongolian medical warm acupuncture has significant efficacy in treating insomnia. The paper evaluates the role of Mongolian medical warm acupuncture in treating insomnia by investigating the Mongolian medicine syndromes and conditions, Pittsburgh sleep quality index, and polysomnography indexes. Method. The patients were diagnosed in accordance with International Classification of Sleep Disorders (ICSD-2). The insomnia patients were divided into the acupuncture group (40 cases) and the estazolam group (40 cases). The patients underwent intervention of Mongolian medical warm acupuncture and estazolam. The indicators of the Mongolian medicine syndromes and conditions, Pittsburgh sleep quality index (PSQI), and polysomnography indexes (PSG) have been detected. Result. Based on the comparison of the Mongolian medicine syndrome scores between the warm acupuncture group and the drug treatment group, the result indicatedP < 0.01 . The clinical efficacy result showed that the effective rate (85%) in the warm acupuncture group was higher than that (70%) in the drug group. The total scores of PSQI of both groups were approximated. The sleep quality indexes of both groups decreased significantly (P < 0.05 ). The sleep quality index in the Mongolian medical warm acupuncture group decreased significantly (P < 0.01 ) and was better than that in the estazolam group. The sleep efficiency and daytime functions of the patients in the Mongolian medical warm acupuncture group improved significantly (P < 0.01 ). The sleep time was significantly extended (P < 0.01 ) in the Mongolian medical warm acupuncture group following PSG intervention. The sleep time during NREM in the Mongolian warm acupuncture group increased significantly (P < 0.01 ). The sleep time exhibited a decreasing trend during REM and it decreased significantly in the Mongolian warm acupuncture group (P < 0.01 ). The percentage of sleep time in the total sleep time during NREM3+4 in the Mongolian medical warm acupuncture group increased significantly. Conclusion. Mongolian medical warm acupuncture is efficient and safe in treating insomnia. It is able to better improve the patients' sleep time and daytime functions. It is better than that in the estazolam group following drug withdrawal in terms of improving the sleep time. It is more effective in helping the insomnia patients than hypnotics.